MAIN FACTORS DRIVING SOCIAL PUBLIC SERVICES IN INTERNATIONAL CONTEXT - Mihaela, GHENTA (Strategii Manageriale)
Literature and the latest reports point out that not only in Europe, but all over the world there is a growing demand for social services. As social needs have diversified, the number of potential users of social services has increased and this has generated increased complexity of social services. This paper highlights some of the results of a study conducted by the author in the doctoral studies program. One of the aims of this study was to identify the main factors that cause the current configuration of social services at global level. The research analysed the demographic changes and the impact of the crisis in social services for Europe, the United States of America (USA) and Japan based on statistical data provided by the national statistics institutes for the regions considered. The results highlight the necessity of continuous development and reconfiguration of social services in order to meet the social and economic demands and to ensure a better organisation of these type of services.